TYPE 2 DIABETES AND CARDIOVASCULAR COMPLICATIONS: IS IT POSSIBLE TO IMPROVE PROGNOSIS BY GLUCOSE LOWERING THERAPY? - Zh. D. Kobalava; G. К. Kiyakbaev (Российский кардиологический журнал)
Regardless the fact that type 2 diabetes (DM2) is related to higher risk of cardiovascular diseases (CVD) development and complications, incl. heart failure (HF), usage of the most of glucose lowering drugs (GLD) does not only improve life prognosis, but might increase the risk of HF. Inhibitors of SGLT2 (gliflozines), a novel group of GLD with a unique non-insulin dependent mechanism of action, in a range of large randomized trials passed not only the obligatory test on cardiovascular safety, but have demonstrated ability to decrease the risk of combination endpoint development (cardiovascular mortality, non-fatal MI and strokes) and possibility for HF hospitalization. The conclusions of randomized trials are confirmed by real clinical practice of DM2 patients management, analyzed in large multicenter trials CVD-REAL, CVD-REAL-2. Inthese trials, first time prescribed SGLT2 inhibitors (in Europe, in most cases dapagliflozin) showed significant benefits for other classes of firstly prescribed GLD in a matter of hospitalization risks for HF or all-cause mortality. However, the total period of the gliflozines usage is not that long, so an answer to the question on stability of their effects in broader perspective is expected by the end of ongoing trials in patients with high cardiovascular risk and in HF patients, including those with no DM2.